Comparison of Solid Self-Nanoemulsifying Systems and Surface-Coated Microspheres: Improving Oral Bioavailability of Niclosamide - Baek K; Woo MR; ud Din F; Choi YS; Kang MJ; Kim JO; Choi HG; Jin SG (International Journal of Nanomedicine, 2024)
Kyungho Baek,1 Mi Ran Woo,2 Fakhar ud Din,3 Yong Seok Choi,4 Myung Joo Kang,4 Jong Oh Kim,5 Han-Gon Choi,2 Sung Giu Jin1 1Department of Pharmaceutical Engineering, Dankook University, Cheonan, South Korea; 2College of Pharmacy, Hanyang University, Ansan, South Korea; 3Department of Pharmacy, Quaid-I-Azam University, Islamabad, Pakistan; 4College of Pharmacy, Dankook University, Cheonan, South Korea; 5College of Pharmacy, Yeungnam University, Gyeongsan, South KoreaCorrespondence: Sung Giu Jin; Han-Gon Choi, College of Pharmacy, Hanyang University, 55 hanyangdaehak-ro, Sangnok-gu, Ansan, 15588, South Korea, Tel +82 41 550-3558 ; +82 31 400-5802, Fax +82 41 559 7945 ; +82 31 400 5958, Email sklover777@dankook.ac.kr; hangon@hanyang.ac.krPurpose: This study aimed to develop a solid self-nanoemulsifying drug delivery system (SNEDDS) and surface-coated microspheres to improve the oral bioavailability of niclosamide.Methods: A solubility screening study showed that liquid SNEDDS, prepared using an optimized volume ratio of corn oil, Cremophor RH40, and Tween 80 (20:24:56), formed nanoemulsions with the smallest droplet size. Niclosamide was incorporated into this liquid SNEDDS and spray-dried with calcium silicate to produce solid SNEDDS. Surface-coated microspheres were prepared using sodium alginate and poloxamer 407 and optimized through solubility and dissolution tests. Scanning electron microscopy, differential scanning calorimetry, and X-ray diffraction were used to evaluate the physicochemical properties of the prepared solid SNEDDS, surface-coated microspheres, and the drug alone. The solubility, dissolution, and oral bioavailability were also assessed.Results: Physicochemical evaluation demonstrated that niclosamide was converted to an amorphous state in the Solid SNEDDS formulation, with enhanced solubility and oral bioavailability. In comparison to niclosamide alone, solid SNEDDS exhibited an increase in drug solubility (approximately 2500-fold vs 158-fold) and oral bioavailability (approximately 10-fold vs 1.65-fold), significantly outperforming surface-coated microspheres.Conclusion: This solid SNEDDS formulation may be an excellent candidate for niclosamide with improved oral bioavailability for repurposing. Keywords: niclosamide, microsphere, solid SNEDDS, dissolution, crystallinity, oral bioavailability